Characterizations of Positive Operator-Monotone Functions and Monotone Riemannian Metrics via Borel Measures - Pattrawut Chansangiam; Sorin V. Sabau (My University, 2019)
We show that there is a one-to-one correspondence between positive operator-monotone functions on the positive reals, monotone Riemannian metrics, and finite positive Borel measures on the unit interval. This correspondence appears as an integral representation of weighted harmonic means with respect to that measure on the unit interval. We also investigate the normalized/symmetric conditions for operator-monotone functions. These conditions turn out to characterize monotone metrics and Morozowa–Chentsov functions as well. Concrete integral representations of such functions related to well-known monotone metrics are also provided. Moreover, we use this integral representation to decompose positive operator-monotone functions. Such decomposition gives rise to a decomposition of the associated monotone metric.
Keywords: Operator (biology); Pseudo-monotone operator; Unit interval; Representation; Mathematical Inequalities and Applications